TRANSFORMASI PERILAKU INDUSTRI DAN IMPLEMENTASI SYARIAH PADA UMKM HALAL DI ERA DIGITAL: Studi Kasus Umkm Halal “Dapoer Yesi” Di Kota Lhokseumawe - Malahayatie; Azkia Munira (Institut Agama Islam K.H. Sufyan Tsauri, 2026)
Industrial behavior has undergone a significant transformation from conventional market frameworks to adaptations required by digital disruption, with meaningful implications for SME actors, particularly in the halal industry sector. This study aims to investigate the dynamics of industrial behavior changes concerning perfect competition, imperfect competition, and the era of digital disruption, and to relate these changes to the implementation of Sharia principles in halal SMEs. The methodology employed is qualitative descriptive, using literature review and field observation. The field study focuses on the home-based cake business “Dapoer Yesi” located in Lhokseumawe. The findings indicate that halal SME industrial practices successfully integrate efficiency, technological innovation, and Sharia values throughout business operations. Despite challenges related to regulations and accessibility of halal certification information, dedication to halal-thayyib principles remains strong among SME actors. This study highlights the need for supportive policies aimed at promoting digitalization and facilitating halal certification, enabling halal SMEs to grow and compete ethically and effectively in an evolving market landscape.